Design and analysis of the multi-port converter based power enhancement for an integrated power generation system using predictive energy amendment algorithm - Madhana, R.; Mani, Geetha (Frontiers in Energy Research, 2022)
The power quality analysis aims to identify electricity consumers to enhance quality using power converters. The study examines the interactions between loads, power networks, and various power quality enhancement technologies. In particular, modern controllers are used in a unified structure to build a novel DC-DC converter for renewable hybrid power generation. Also, the modified DC-DC converter requires efficient power management and a balanced supply-demand system. This work focuses on creating a multi-port power electronic converter that can be used to integrate numerous renewable energy sources with varying source and load characteristics. When surplus energy is available in photovoltaics, the proposed converter may conduct maximum power point tracking control for the system and regulate the charging and discharging of the battery. Therefore, the modified converter should reduce the static level error and maximum overshoot. This paper proposed a multi-port converter that ensures high energy efficiency. Moreover, the proposed circuit driven by the predictive energy amendment algorithm ensures superior energy harvesting from different ports while maintaining high power, transfer efficiency and reliability. The dynamically generated duty cycles avoid cross-regulation and regulate the various port voltages irrespective of the environmental conditions. The impact of fluctuation can be significantly reduced by combining renewable energy sources with the statistical capacity to counteract each other, enhancing the system's overall reliability and utility. Furthermore, the proposed converter has the potential to lower system cost and size owing to reducing switch counts while increasing efficiency and reliability. The MATLAB/SIMULINK environment examined and evaluated the proposed architecture and control technique, proven the feasibility and its superior characteristics demonstrates the steady-state error of 0.284 %, total harmonics distortion of about 0.13 %, and system efficiency of 96.2 %. Moreover, the numerical results proven that the proposed controller efficiency is 6.88 % greater than that of conventional PID controller.